Ethnic Minority Development in Vietnam : A Socioeconomic Perspective - Baulch, Bob (The World Bank, 2002)
Baulch, Chuyen, Haughton, and Haughton examine the latest quantitative evidence on disparities in living standards between and among different ethnic groups in Vietnam. Using data from the 1998 Vietnam Living Standards Survey and 1999 Census, they show that Kinh and Hoa ("majority") households have substantially higher living standards than "minority" households from Vietnam's other 52 ethnic groups. Subdividing the population into five broad categories, the authors find that while the Kinh, Hoa, Khmer, and Northern Highland minorities have benefited from economic growth in the 1990s, the growth of Central Highland minorities has stagnated. Disaggregating further, they find that the same ethnic groups whose living standards have risen fastest are those that have the highest school enrollment rates, are most likely to intermarry with Kinh partners, and are the least likely to practice a religion. The authors then estimate and decompose a set of expenditure regressions which show that even if minority households had the same endowments as Kinh households, this would close no more than a third of the gap in per capita expenditures. While some ethnic minorities seem to be doing well with a strategy of assimilating (both culturally and economically) with the Kinh-Hoa majority, other groups are attempting to integrate economically while retaining distinct cultural identities. A third group comprising the Central Highland minorities, including the Hmong, is largely being left behind by the growth process. Such diversity in the socioeconomic development experiences of the different ethnic minorities indicates the need for similar diversity in the policy interventions that are designed to assist them.